(untitled) (Research, Society and Development, 2022)
Periodontitis is a disease that affects the supporting tissues around the tooth that leads to tissue destruction and tooth loss, due to microbial inflammation caused by dental biofilm. Periodontitis, in the 1999 Classification, is divided into chronic and aggressive, and can be further divided into localized and generalized. The objective of this scope is to carry out an integrative literature review to verify the importance and effectiveness of laser therapy and photodynamic therapy in the treatment of periodontitis. In the treatment of periodontitis, commitment must be made by both the professional and the patient, who must maintain strict oral hygiene while the dentist performs a supra and subgingival scaling "if necessary" in the office, associated with root planing and a systematic periodic control. Photodynamic therapy is the association of laser light with a photoactive dye, the photosensitizer that with the laser radiates to the bacterial cells generating energy in the oxygen molecules of the bacterial cell forming a reactive oxygen, the singlet oxygen that destroys the biological system, causing death of the cell, causing the best disinfection of the root surface. Dyes applied to epithelial and connective tissue do not cause damage to these tissues, and chromophore dyes such as methylene blue and toluidine blue can be used in the treatment of periodontitis and peri-implantitis, as they affect Gram positive and Gram negative bacteria.